Algoritma Branch and Bound untuk Driver Assignment pada Aplikasi Simulasi Taksi Online - Arlynston Liadi; Andreas Handojo; Tanti Octavia (Jurnal Infra, 2020)
Online taxi is one of the developments in technology that is currently being used by the wider community. Online taxis also have positive impacts such as drivers and passengers can know each other's location accurately, passengers can see drivers and vehicle information accurately, and passengers can easily find transportation to travel to other places. However, in reality requests from passengers appear randomly in different locations, so we need an application that can optimize the assignment between drivers and passengers..Applications are made with the python, html, and javascript programming languages, with django as a framework, bootstrap 3 for the front end menu, the Google maps API to get time and distance, as well as the front end in the online map section, and mySQL as the database used.The end result of this application is an assignment for drivers and passengers using a web-based branch and bound algorithm that can minimize pickup costs and waiting times by calculating the total combination of mileage, travel time, and the number of trip drivers on an online taxi.